Numerical prediction of velocity, pressure and shear rate distributions in stenosed channels - Fernandes, Carla S. (2012)
Wall shear rates and pressure developed in circulatory system play an important role on the development of some clinical problems such as atherosclerosis and thrombosis. In the present work, blood flow behaviour was numerically studied in simplified domains and several relevant local properties were determined. The stenosis degree was varied in the distinct studied channels and blood rheology was described by three different models – constant viscosity, power-law model and Carreau model. Pressure attains maximum values in the wall of the atheroma and shear rates achieved maximum values in the top of the atheroma. It was also observed that, with the studied flows, the predictions for velocity and shear rate using non-Newtonian models were very similar. This observation can be explained by the magnitude of the obtained shear rates.